Examining the Equilibrium Relationship Between the Shanghai 50 Stock Index Futures and the Shanghai 50 ETF Options Markets. Issue 11 (2nd September 2018) - Wang, Jinzhong; Kang, Hao; Xia, Fei; Li, Guowei
ABSTRACT: Based on the put-call-futures parity model, this article studies the equilibrium relationship between the Shanghai 50 stock index futures and the Shanghai 50 Exchange-Traded Fund (ETF) options markets by analyzing the arbitrage opportunities and profits between these two derivative markets. This article reveals that the cost spread, option volatility, days from the expiration date, moneyness of options, trading strategy, and policy factors all have a great impact on the arbitrage profits and opportunities. In addition, significant arbitrage profits and opportunities indicate violations of put-call-futures parity. Although no equilibrium relationship exists between the Shanghai 50 stock index futures and the Shanghai 50 ETF options markets, efficiency in these markets has gradually improved.